Performing migration in Vienna: The Volkstheater trilogy. (1st November 2019) - Angelaki, Vicky
AbstractThis article is concerned with the example of Vienna's Volkstheater in asking how major European cultural institutions might affectively and effectively engage with the refugee crisis and asylum seeking especially following what has become known as the 'Long Summer of Migration' (2015). It discusses what we might describe as the 'Migration Trilogy' of pieces co-developed by Yael Ronen and the performer ensembles involved, namely, the plays Lost and Found, Niemandsland and Gutmenschen.